Congenital cystic adenomatous malformation: a case report and a literature review - Račaitė, Julita; Šumkovskaja, Alina; Arlauskienė, Audronė; Pilypienė, Ingrida; Landsbergytė-Bukauskienė, Elena (Acta medica Lituanica, 2018)
Background. A congenital cystic adenomatoid malformation (CCAM) is a foetal pulmonary development abnormality caused by airway dysgenesis that is characterized by cystic or adenomatous lesions in the terminal bronchioles. The size of the mass, the degree of the mediastinal shift, and the presence of hydrops and polyhydramnios can all affect the severity of a case. Treatment can be initiated at early stages by applying prenatal and postnatal methods. Because CCAM is a rare pathology that is often only accidentally diagnosed during routine ultrasounds, we would like to share our case report to enrich the literature on this pathology and to present a case successfully treated at our hospital. Materials and methods. A patient with her first multiple pregnancy was seen for prenatal care and her first ultrasound at 17 weeks of gestation. One of the twins was diagnosed with a congenital cystic adenomatoid malformation of the left lung. At 20 weeks of gestation, an enlarged left lung with small cysts, a compressed right lung, a compressed and displaced heart, and oligohydramnios were observed. At 28 weeks of gestation, a fetoplacental circulation disorder appeared. At 32 weeks of gestation, due the unstable condition of the affected foetus, the twins were delivered via a C-section. The treatment of the newborn included antibiotics, caffeine citrate, and breathing therapy. Results and conclusions. CCAM are often diagnosed by accident when performing routine pregnancy ultrasound examinations. CT is the most reliable X-ray-based examination method for confirming a diagnosis. When CCAM is suspected in the foetus, amniocentesis and cariotype identification are performed, but chromosomal anomalies related to CCAM are often not identified. Currently, the best treatment results have been achieved by applying combined prenatal therapy and early surgical treatment.